Diagnosis of invasive fungal diseases in haematology and oncology: 2018 update of the recommendations of the infectious diseases working party of the German society for hematology and medical oncology (AGIHO) - Ruhnke, Markus; Buchheidt, Dieter; Heußel, Claus Peter (Mycoses, 2018)
Invasive fungal diseases (IFD) are a primary cause of morbidity and mortality in patients with haematological malignancies. These infections are mostly life-threatening and an early diagnosis and initiation of appropriate antifungal therapy are essential for the clinical outcome. Most commonly, Aspergillus and Candida species are involved. However, other Non-Aspergillus moulds are increasingly identified in case of documented IFD. For definite diagnosis of IFD, a combination of diagnostic tools have to be applied, including conventional mycological culture and non-conventional microbiological tests such as antibody/antigen and molecular tests, as well as histopathology and radiology. Although varying widely in cancer patients, the risk of invasive fungal infection is highest in those with allogeneic stem cell transplantation and those with acute leukaemia and markedly lower in patients with solid cancer. Since the last edition of Diagnosis of Invasive Fungal Diseases recommendations of the German Society for Hematology and Oncology in 2012, integrated care pathways have been proposed for the management and therapy of IFDs with either a diagnostic driven strategy as opposed to a clinical or empirical driven strategy. This update discusses the impact of this additional evidence and effective revisions.
Gesehen am 30.04.2019